Implementation of STEAM in Preschool as a 21st-Century Learning Innovation - Nurhusni Kamil; Evi Anggraeni HR (JOYCED: Journal of Early Childhood Education, 2023)
STEAM in the world of education is no stranger. Many countries in the world have implemented learning using this approach. STEAM is considered to influence learning because STEAM is a combination of several sciences that become one unit. One of the benefits of learning STEAM is that children are taught to be able to solve the problems they are facing. The use of technology that is very supportive makes this one of the supporting factors. The research method used in this study was qualitative, with a sample of 12 children aged 4-5 years who were selected using a purposive sampling technique. The research was conducted at Sungai Rumbai Kindergarten IB in Jorong Kampung Baru. This study aimed to see the implementation of STEAM in Preschool as a 21st Century Learning Innovation. Data collection techniques used non-test techniques obtained from interviews, observations, and documentation obtained from class teachers. The study results show that STEAM has been implemented in TK IB Sungai Rumbai through various activities.